The Meaning of Early Adolescent Existence on Social Media through the Use of Second Accounts as a Reinforcement of Socio-Cultural Change Material in Social Studies Learning - Rifqi Al Amin; Ali imron; Sugiantoro Sugiantoro (LPPM Sekolah Tinggi Ilmu Ekonomi 45 Mataram, 2026)
This study aims to analyze the meaning of early adolescents' existence through the use of a second Instagram account and examine its relevance in Social Studies learning, focusing on socio-cultural change. This study employed a qualitative approach with a phenomenological design, conducted at SMP Negeri 2 Taman, Sidoarjo Regency. Informants consisted of 15 students aged 14–15 selected using a purposive sampling technique. Data were collected through in-depth interviews, observation, and documentation, then analyzed using the interactive model of Miles, Huberman, and Saldana. The results indicate that the second account is interpreted as a digital social space for self-expression, maintaining privacy, achieving psychological comfort, and building self-identity. The primary account functions as a front stage, displaying a self-image according to social needs, while the second account functions as a back stage, allowing for more authentic expression. Driving factors for use include the need for privacy, fear of social judgment, and content restrictions. Impacts include increased comfort in expressing oneself and the risk of overthinking and misunderstanding. In conclusion, the use of a second account reflects adolescents' digital identity management and represents a form of socio-cultural change in the digital era that is relevant as a resource for contextual learning in Social Studies.